Fluorescence Probes for Sensing - Sheshanath V. Bhosale (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The rapid progress in sensor science in recent years has resulted in the development of fluorescence probes with enhanced analytical capabilities. Because of the vast evolution of this research field, therefore, we have decided to combine all the research articles published in "Fluorescence Probes and Sensors" for a Special Issue (SI) book of Sensors which was focusing on the important role sensors play in "Fluorescent Probes and Sensors". Fluorescence novel Probes make an ideal candidate for promising applications in biological analytes and environmental monitoring. Fluorescent probes along with metal complexes have been developed as a new class of fluorophores with excellent properties. This book illustrating the suitability of newly developed sensors for fluorescent analysis applications, as well as describing novel applications of established sensors in solving real life analytical problems.